2001
DOI: 10.1002/1521-4095(200108)13:16<1249::aid-adma1249>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Efficient Post-Polymerization Functionalization of Poly(3,4-ethylenedioxythiophene) (PEDOT) Derivatives on an Electrode Surface

Abstract: First examples of post‐polymerization functionalization of poly(3,4‐ethylenedioxythiophene) (PEDOT) derivatives are reported using tetrathiafulvalene (TTF) as a redox sensitive probe. EDOT derivatives bearing ω‐iodo‐alkyl or ω‐iodo‐polyether chains attached at the ethylenedioxy bridge have been electropolymerized and the resulting polymers have been derivatized using a TTF bearing a thiolate anion liberated under mild conditions. Cyclic voltammetry confirms the rapidity and efficiency of the derivatization pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 31 publications
2
47
0
Order By: Relevance
“…17 The post-polymerization functionalization of PEDOT derivatives has been less explored yet. Besbes et al 18 reported on functionalization of PEDOT derivatives bearing u-iodoalkyl or u-iodo-polyether chains attached at the ethylenedioxy bridges. Lyskawa et al explored the potential of this strategy to prepare modified electrodes for Pb 2þ detection.…”
Section: Introductionmentioning
confidence: 99%
“…17 The post-polymerization functionalization of PEDOT derivatives has been less explored yet. Besbes et al 18 reported on functionalization of PEDOT derivatives bearing u-iodoalkyl or u-iodo-polyether chains attached at the ethylenedioxy bridges. Lyskawa et al explored the potential of this strategy to prepare modified electrodes for Pb 2þ detection.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for choosing an aqueous micellar solution as the growing medium are as follows: these solutions are cost effective, the resulting films are highly scalable, uniform and homogeneous and most importantly the films can be switched reversibly between the transparent and dark blue states over a large number of cycles with little effect on the electrochromic contrast [12][13][14][15]. Similarly post polymerization functionalization of PEDOT is also a relatively less investigated concept [16], owing to the paucity of agents that can functionalize PEDOT. In this regard, here by using a photochemical agent 1-fluoro-2-nitro-4-azidobenzene (FNAB), which is typically used in biochemistry for immobilizing enzymes in polythiophenes [17,18], we functionalized the ethylenedioxy bridge through a simple reaction involving the insertion of the nitrogen of FNAB between C and H of the oxygen containing rings in PEDOT through a nitrene intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis routes of P 1 -TTF and P 2 -TTF. [27] suggested the reason was that the redox processes were partially limited by charge and/or mass transformation in the polymer film. Chemical oxidations of P 1 -TTF and P 2 -TTF were performed by Fe(bpy) 3 (PF 6 ) 3 .…”
Section: Electroactive Propertiesmentioning
confidence: 99%